Enacting Spousal Dominance through Language: An SFL Analysis of Mr. Kirsha in Midaq Alley - Ali Mohammed Saleh Al-Hamzi (Universitas Negeri Semarang, 2026)
This paper investigates the linguistic construction of spousal dominance, especially in the marriage of Mr. and Mrs. Kirsha, in the novel Midaq Alley by Naguib Mahfouz. The approach to this study is underpinned by Systemic Functional Linguistics, focusing on the linguistic construction of patriarchy in the Egyptian culture during the1940s. Compared with various analytical frameworks on one case, the major framework adopted in this analytical study is Systemic Functional Linguistics, illustrating the interplay of the ideational, interpersonal, and textual metafunctions to construct spousal dominance. The results of the dialogic event analysis, which included commands, threats, and moral or religious justifications, following the ethnographic approach developed by Spradley, support the hypothesis that Mr. Kirsha wields his spousal dominance with directive control, moral justification, and authorization, while Mrs. Kirsha resists it with challenges, moral condemnation, and confrontational talk, thus articulating the sociocultural realities of the Egyptian gender discourses.